Indo-Pacific and ASEAN new balances and new challenges for Asian integration and stability - Trân, Thị Liên; Suthiphand Chirathivat 1953-; De, Prabir 1962- (Routledge, Taylor & Francis Group, 2025)
"This book examines Indo-Pacific issues from a Southeast Asian perspective and goes beyond discourses such as ASEAN-China or ASEAN-US-China. It analyses the new regional balances in the ASEAN and Indo-Pacific region at the diplomatic, strategic and economic levels while taking into account the ongoing uncertainty of the international order, reshaped by the post Covid-19 crisis and characterized by the increasingly adversarial China-US relations, the sensitive context of South China Sea and Taiwan crisis and the impact of the war between Russia and Ukraine. It highlights Indo-Pacific not only from a geostrategic angle but an economic one, considering ASEAN amidst competing connectivity strategies and integration challenges. The volume offers an inclusive outlook capturing diversity and convergence of strategies in a key region where the stage of tomorrow's global order will be decided. It will be of great interest to scholars and researchers of politics and international relations and Area Studies, especially Southeast Asian Studies and Indo-Pacific Studies."
Includes bibliographical references and index
Keywords: ASEAN; Interregionalism / Southeast Asia; Interregionalism / Indo-Pacific Region; Asian cooperation; Southeast Asia / Foreign relations / Indo-Pacific Region; Indo-Pacific Region / Foreign relations / Southeast Asia